Components of antenatal care received by women in fishing communities on Lake Victoria, Uganda; a cross sectional survey - Ali Ssetaala; Joan Nabawanuka; Gideon Matovu; Nusula Nakiragga; Judith Namugga; Phiona Nalubega; Henry Lutalo Kaluuma; Kundai Chinyenze; Katrina Perehudoff; Kristien Michielsen; Bernard Bagaya; Matt Price; et al. (BMC, 2020)
Abstract Background Uganda has one of the highest maternal deaths at a ratio of 336 per 100,000 live births. As Uganda strives to achieve sustainable development goals, appropriate antenatal care is key to reduction of maternal mortality. We explored women's reported receipt of seven of the Uganda guidelines components of antenatal care, and associated factors in hard to reach Lake Victoria island fishing communities of Kalangala district. Methods A cross sectional survey among 486 consenting women aged 15-49 years, who were pregnant at any time in the past 6 months was conducted in 6 island fishing communities of Kalangala district, Uganda, during January-May 2018. Interviewer administered questionnaires, were used to collect data on socio-demographics and receipt of seven of the Uganda guidelines components of antenatal care. Regression modeling was used to determine factors associated with receipt of all seven components. Results Over three fifths (65.0%) had at least one ANC visit during current or most recent pregnancy. Fewer than a quarter of women who reported attending care at least four times received all seven ANC components [(23.6%), P < 0.05]. Women who reported receipt of ANC from the mainland were twice as likely to have received all seven components as those who received care from islands (aOR = 1.8; 95% CI:0.9-3.7). Receipt of care from a doctor was associated with thrice likelihood of receiving all components relative to ANC by a midwife or nurse (aOR = 3.2; 95% CI:1.1-9.1). Conclusions We observed that the delivery of antenatal care components per Ugandan guidelines is poor in these communities. Cost effective endeavors to improve components of antenatal care received by women are urgently needed. Task shifting some components of ANC to community health workers may improve care in these island communities. Trial registration PACTR201903906459874 (Retrospectively registered).